Adjunctive treatment of leptospirosis with corticosteroids : a case report = Liječenje leptospiroze kortikosteroidima : prikaz bolesnika - Miklaušić, Božana (Array, 2020)
Leptospirosis is one of the most globally widespread zoonosis caused by pathogenic spirochetes from genus Leptospira spp. Icteric leptospirosis is a severe form of the disease which affects 5-15% of patients with leptospirosis, is often rapidly progressive and has a high mortality rate. Early diagnosis of leptospirosis is crucial for initiation of adequate antimicrobial therapy in order to prevent the advent of complications and reduce mortality. Literature offers an increasing amount of evidence that early application of corticosteroids affects the course of the disease, prevents the onset of multiorgan failure, reduces mortality and reduces the duration of hospitalization. This paper is a case report of a patient with severe icteric leptospirosis who was treated with antimicrobial and corticosteroid therapy. The patient recovered fully, with no remaining morbidity after the severe disease.